Assessment of the Institute for Research Design in Librarianship, Phase 2: Impact on the Research Productivity and Careers of Academic Librarians - Albarillo, Frans; Kennedy, Marie R.; Brancolini, Kristine R. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – This article reports on the qualitative phase of a two-phase sequential mixed-methods study to assess the first six years of the Institute for Research Design in Librarianship (IRDL), a continuing education program for academic and research librarians. The study is designed to assess the effectiveness of IRDL in meeting short-term and long-term programmatic objectives related to the research productivity, job performance, and professional identities of the participants in the program.Methods – In this second part of a two-phase study, the authors conducted focus group and individual interviews with 37 IRDL participants (hereafter called Scholars) and coded the resulting transcripts. The first phase of the study surveyed all 124 program participants; the results were reported in an earlier article in this journal. The second-phase interviews were conducted and then coded using a deductive process. The researchers identified transcript excerpts that explored the concepts of research productivity, job performance, and identity as a researcher. Each of these concepts was further sub-coded to explore the four sources of self-efficacy, as described in Albert Bandura’s theory: mastery experiences; verbal or social persuasion; vicarious experiences; and physiological and affective states.Results – The majority of the conversations in both the in-depth individual interviews and the focus group interviews centered around research productivity; approximately 70% of the transcript excerpts from focus groups and 55% of the individual interviews addressed issues related to productivity. Participants also discussed the impact of IRDL on their job performance and their identify as researchers. Gaining research confidence had a notable positive impact on job performance related to classroom teaching and supporting researchers. Within these areas of conversation, all sources of self-efficacy were evident, but the most frequently noted were influences related to mastery learning and social persuasion, through mentorship and becoming part of a peer research community.Conclusion – The findings from the focus groups and in-depth interviews deepen the meaning of the results from the quantitative phase of our IRDL assessment research. The participants in the study reported both frustration and satisfaction with conducting their research. A supportive environment focused on helping librarians gain needed research skills, practice those skills, and become part of a research community contributes to research confidence and productivity, improved job performance, and identity as a researcher. The findings of this study have implications for developing librarians as researchers, including the importance of a supportive work environment, research mentoring, and the positive influence of becoming part of a research community.